Smart card research and advanced applications : 13th International Conference, CARDIS 2014, Paris, France, November 5-7, 2014. Revised selected papers /: 13th International Conference, CARDIS 2014, Paris, France, November 5-7, 2014. Revised selected papers. (2015) - Unknown
No abstract available